Founding partisans : Hamilton, Madison, Jefferson, Adams and the brawling birth of American politics - Brands, H. W. (Doubleday, 2023)
"From bestselling historian and Pulitzer Prize finalist H. W. Brands, a revelatory history of the shocking emergence of vicious political division at the birth of the United States Founding Partisans is a lively narrative of the early years of the republic as the Founding Fathers fought one another with competing visions of what our nation would be. To the framers of the Constitution, political parties were an existential threat to republican virtues. They had suffered the consequences of partisan politics in Britain before the American Revolution, and they wanted nothing similar for America. Yet parties emerged even before the Constitution was ratified, and they took firmer root in the following decade. The first party, the Federalists, formed around Alexander Hamilton and his efforts to overthrow the Articles of Confederation. Thomas Jefferson and the opposition organized as the Antifederalists, the precursor to the Republicans. The two factions wrestled as George Washington tried to remain above the fray. John Adams, however, our second president, was an avowed Federalist, and very much in the scrum. The country's first years unfolded in a contentious spiral of ugly elections and blatant violations of the Constitution. Still, peaceful transfers of power continued, and the nascent country made its way toward global dominance, against all odds. Founding Partisans is a powerful reminder that fierce partisanship is a problem as old as the republic, one we've survived time and time again"--